Trends, Advances, and Future Directions in Fuel Cell Electric Vehicle Performance: A Bibliometric Analysis Using the PAGER Framework - Yusuf Dewantoro Herlambang; Nanang Apriandi; Komang Metty Trisna Negara; Rani Raharjanti; Lily Maysari Angraini; Abdul Syukur Alfauzi; Marliyati Marliyati (Automotive Experiences, 2025)
The global shift toward sustainable transportation has positioned fuel cell electric vehicles (FCEVs) as a key zero-emission mobility solution. Despite notable technological progress, FCEV adoption faces persistent barriers including high hydrogen production costs, limited infrastructure, and lack of real-world validation. This study employs the Pattern, Advance, Gap, Evidence for Practice, and Research Recommendation (PAGER) framework to conduct a comprehensive bibliometric analysis of 200 peer-reviewed publications from 2005 to 2024, focusing on performance trends, technological advancements, research gaps, practical applications, and future research directions. The analysis uses Scopus data and VOSviewer for visualization and thematic mapping to identify three distinct research phases: early exploration, gradual refinement, and rapid technological maturity. Key findings highlight advancements in energy management strategies, hybrid powertrain integration, and hydrogen storage optimization. However, critical gaps remain in economic modeling, behavioral adoption analysis, and infrastructure scalability. This study offers a structured roadmap for future research and practice, emphasizing the need for dynamic total cost of ownership models, interdisciplinary policy interventions, and real-world pilot projects. The findings serve as a strategic reference for academics, industry stakeholders, and policymakers to accelerate the global transition to sustainable FCEV-based transportation systems.